تأثير بعض المعاملات في تحسين نسبة إنبات بذور الغار النبيل Laurus nobilis ,L في بعض مواقع الساحل السوري - غندور, وفاء; عيسى, عفيفة; حمدكو, نوال (Latakia University Journal -Biological Sciences Series, 2019)
أجريت هذه الدراسة بهدف الحصول على أسرع وأعلى نسبة إنبات لبذور الغار النبيل,L. Laurus nobilis. نفذت التجربة على 400 بذرة، قسمت الى 4 مجموعات، واستخدمت في أربع تجارب حقلية هي: تجربة الشاهد– تجربة المعاملة بحمض الكبريت المركز– تجربة المعاملة بالخدش الميكانيكي– تجربة المعاملة بالتنضيد البارد الرطب. أظهرت نتائج الدراسة نجاح طريقة المعاملة بالتنضيد البارد الرطب وتفوقها في رفع نسبة إنبات بذور الغار إلى 99% وتسريعه . لم تنبت أي بذرة من بذور الغار عند المعاملة بحمض الكبريت المركز أي أن حمض الكبريت لعب دوراً مخرباً للنسج . وبينت الدراسة أيضاً أن نسبة الإنبات في تجربة المعاملة بالخدش الميكانيكي 84%. يمكن استخدام هذه النتائج في تسريع الإنبات واختصار الزمن اللازم له، ومن ثم توفير العدد الكافي من الغراس اللازمة ليستفاد منه بيئياً واقتصادياً. This study was conducted in order to obtain faster and higher proportion of seeds germination of Laurus nobilis,L. The experiment was applied using 400 seeds ,which were divided into four groups : control; treatment with concentrated sulfuric acid (H2SO4 ); mechanical treatment; and treatment with moist cold stratification. The results showed the success of the moist cold stratification method and its superiority in raising the proportion of germination to 99% with its acceleration. Seeds weren’t germinated with sulfuric acid concentrated method, because that sulfuric acid plays destroying role of tissues. Results also showed that the proportion of germination arrived to 84% with the effect of mechanical scratch treatment. We can use these results for getting fast germination and saving enough number of seedlings for environmental and economic benefits.